Synthesis of Modified Poly(vinyl Alcohol)s and Their Degradation Using an Enzymatic Cascade. Issue 18 (9th February 2023) - von Haugwitz, Gerlis; Donnelly, Kian; Di Filippo, Mara; Breite, Daniel; Phippard, Max; Schulze, Agnes; Wei, Ren; Baumann, Marcus; Bornscheuer, Uwe T.
Abstract: Poly(vinyl alcohol) (PVA) is a water‐soluble synthetic vinyl polymer with remarkable physical properties including thermostability and viscosity. Its biodegradability, however, is low even though a large amount of PVA is released into the environment. Established physical‐chemical degradation methods for PVA have several disadvantages such as high price, low efficiency, and secondary pollution. Biodegradation of PVA by microorganisms is slow and frequently involves pyrroloquinoline quinone (PQQ)‐dependent enzymes, making it expensive due to the costly cofactor and hence unattractive for industrial applications. In this study, we present a modified PVA film with improved properties as well as a PQQ‐independent novel enzymatic cascade for the degradation of modified and unmodified PVA. The cascade consists of four steps catalyzed by three enzymes with in situ cofactor recycling technology making this cascade suitable for industrial applications. Abstract : Biodegradation of water‐soluble PVA by microorganisms is slow and frequently involves pyrroloquinoline quinone (PQQ)‐dependent enzymes. In this study, we present a modified PVA film with improved properties as well as a PQQ‐independent novel enzymatic cascade consisting of a lipase, an alcohol dehydrogenase and a Baeyer–Villiger monooxygenase for the degradation of modified and unmodified PVA.